Perceptions, Motivation and Expectations of Rural Female Secondary School Students about their Academic Future - Haneef, Anam; Buzdar, Muhammad Ayub; Rasool, Shafqat (Annals of Human and Social Sciences, 2023)
This study aims to explore Student’s Perceptions, Motivation and Expectation about academic future is a fast growing field of research in educational setup. It exerts great influences upon student’s achievement, and student’s learning process. The present study attempted to investigate secondary school student perceptions expectation and motivation about their academic future and it was designed to explore the relationship between female student’s motivation and their expectation, of secondary school student in rural areas in Pakistani context. Survey method was used to collect data from the respondents of this study. The nature of the study was descriptive and correlational which aimed at looking into perception, motivation and expectation of female rural students. A total number of 600 secondary school students were selected by stratified random sampling from six secondary school students of the district Faisalabad and jhang. Questionnaire were comprising 37 items was developed for study. Mean score of each item of questionnaire was calculated to find central tendency of responses. Group differences and their mean were analyzed by using frequencies test and independent t-test to find out mean differences. The t-test results indicated that there was significant difference on mean score among groups. Independent t-test result concluded that there was significant difference on mean score among groups. It was concluded from the study that students should explore themselves by showing their interest in order to choose their future. Parents should be more supportive rather than imposing their perception on their children. Student center curriculum should be developed in Pakistan.